The stability analysis of a system with two delays - Erman, Sertaç; Kodal Sevindir, Hülya; Demir, Ali (Springeropen, 2018)
This paper presents new results of stability analysis for a linear system with two delays. We attempt to determine the asymptotic stability regions of the system in a parameter space by using D-partition method. Moreover, some stability and instability conditions in terms of coefficient inequalities have been obtained for the system.
WOS: 000437760000003
Keywords: Stability Analysis; Delay Differential Equations; Multiple Delays